2006
DOI: 10.1111/j.1745-6592.2006.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of DNAPL Source Depletion Technologies at 59 Chlorinated Solvent‐Impacted Sites

Abstract: Performance and rebound of intensive source depletion technologies were evaluated at 59 chlorinated solvent sites where remediation targeted dense non–aqueous phase liquid (DNAPL) source zones. The four technologies included in the study are chemical oxidation, enhanced bioremediation, thermal treatment, and surfactant/cosolvent flushing. Performance was evaluated by examining temporal ground water concentration data before and after source remediation was performed. Results indicated that all four technologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
156
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(166 citation statements)
references
References 20 publications
9
156
1
Order By: Relevance
“…For example, Suchomel and Pennell (2006) conducted flow-cell experiments to examine the impact of surfactant-enhanced solubilization on mass-fluxreduction/mass-removal behavior. Several examples of end-point analyses based on field studies have recently been reported (Brooks et al, 2004;Childs et al, 2006;McGuire et al, 2006;Brusseau et al, 2007). The end-point analysis approach provides critical information for evaluating the impact of a source-zone remediation effort on mass flux.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Suchomel and Pennell (2006) conducted flow-cell experiments to examine the impact of surfactant-enhanced solubilization on mass-fluxreduction/mass-removal behavior. Several examples of end-point analyses based on field studies have recently been reported (Brooks et al, 2004;Childs et al, 2006;McGuire et al, 2006;Brusseau et al, 2007). The end-point analysis approach provides critical information for evaluating the impact of a source-zone remediation effort on mass flux.…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that monitored contaminant concentrations for extended periods beyond completion of source depletion activities have observed some levels of concentration rebound (Goldstein et al, 2004;Gomez-Lahoz et al, 1994;McGuire et al, 2006). The prevalent rebound occurrence could result from heterogeneous subsurface permeability, volatilization of contaminants into the vadose zone, intra-aggregate diffusion, and sorption on aquifer materials (Abriola et al, 2004;Gomez-Lahoz et al, 1994;McGuire et al, 2006;Wilkins et al, 1995). The micropore-sorbed contaminants are not readily available for external removal/destruction by physical, chemical, and biological processes during the period of engineered remediation (which typically lasts weeks to months).…”
Section: Long-term Preservation Of Organic Contaminants and Implicationsmentioning
confidence: 99%
“…In a survey of 59 chlorinated solvent sites (McGuire et al, 2005) where active source treatment technologies -chemical oxidation, enhanced bioremediation, thermal treatment, and surfactant/co-solvent flushing -were implemented, none of the technologies were able to achieve maximum contaminant levels (MCLs) 1 to 5 years after the treatment. Furthermore, despite the fact that active technologies no longer offer the cost-benefits required to continue operation at many of these sites, discontinuing source treatment is not considered an acceptable option due to the potential for the residual mass to act as a long-term source of low-level groundwater contamination.…”
Section: Problem Statementmentioning
confidence: 99%